2007
DOI: 10.1086/519498
|View full text |Cite
|
Sign up to set email alerts
|

On the Consumption of Negative Feelings

Abstract: How can the hedonistic assumption (i.e., people's willingness to pursue pleasure and avoid pain) be reconciled with people choosing to expose themselves to experiences known to elicit negative feelings? We assess how (1) the intensity of the negative feelings, (2) positive feelings in the aftermath, and (3) the coactivation of positive and negative feelings contribute to our understanding of such behavior. In a series of four studies, consumers with either approach or avoidance tendencies (toward horror movies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
224
1
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(242 citation statements)
references
References 37 publications
11
224
1
6
Order By: Relevance
“…Andrade and Cohen (2007), for instance, demonstrated that students who liked to expose themselves to horror movies were more likely to experience both fear and happiness while watching such movies, whereas those who usually avoided horror movies were more likely to experience only fear.…”
Section: Research Articlementioning
confidence: 99%
“…Andrade and Cohen (2007), for instance, demonstrated that students who liked to expose themselves to horror movies were more likely to experience both fear and happiness while watching such movies, whereas those who usually avoided horror movies were more likely to experience only fear.…”
Section: Research Articlementioning
confidence: 99%
“…Akin to hedonic reversals and pleasurable "mind-over-body realizations" in the context of painful food-intake (Rozin, 2000, p. 980), media users may take pleasure in many innate or highly automatic body sensations, which are actually painful or distressing (e.g., Andrade & Cohen, 2007;de Wied, Zillmann, & Ordman, 1994). Horror movies provide one such example.…”
Section: Affective Challengesmentioning
confidence: 99%
“…For example, males may enjoy horror movies more than females as they feel more protected and more capable of withstanding induced fear. Research by Andrade and Cohen (2007) suggests that such a "protective frame-of-mind" indeed moderates the impact of fear-inducing horror movies on enjoyment.…”
Section: Affective Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, with respect to the choose-to-receive phase there is certainly lots of evidence that many people seek out opportunities to experience negative emotions under certain circumstances in which cognitions indicate there is no real threat, such as roller coasters and horror movies (Rozin, Haidt and McCauley, 2008b). The appeal of fear and disgust within the horror genre has long been the subject of theorizing grounded in psychoanalysis (Schneider, 2004;Fahy 2010), but there is also a recent experimental literature investigating when and why people consume negative emotions such as disgust (Andrade and Cohen, 2007;Tamir, 2009). Nonetheless, no prior research explicitly tests whether preferences to seek out disgusting stories are sufficiently general to act as a force of cultural selection of stories.…”
mentioning
confidence: 99%